Minute masterpieces : study of a late fifteenth-century French Book of Hours (CBL WMs 89) - Yvard, Catherine (Trinity College (Dublin, Ireland). Department of History of Art and Architecture, 2005)
This thesis provides a full monographic study of a previously unpublished manuscript book of hours for the use of Rouen now in the collection of the Chester Beatty Library (WMs 89). The manuscript is examined from a stylistic, iconographical and codicological point of view with the aim of establishing the stages and circumstances of its execution, and its location in the context of late 15~h century French manuscript production. It is shown that it was written and received its secondary decoration in Rouen ca. 1485-90, and that five artists were involved in its lavish illustrations: one from Rouen (the Master of the Echevinage de Rouen), and four from Tours (Jean Bourdichon, a talented follower of Fouquet, the Master of Jean Charpentier, and another Tourangeau, responsible for the small calendar miniatures). Each miniature is considered in relation to other works assigned to these various artists and to their contemporaries. The origins of these compositions and their impact on later generations of miniaturists are examined. This study also reveals the essential impact that the Prayer book of Charles the Bold (Los Angeles, Getty Mus., ms. 37), painted by the Flemish artist Lievin van Lathem ca. 1469-71, had on the work of the Master of the Echevinage de Rouen. Vol. IV consists in an illustrated Catalogue of Manuscript Books of Hours in Irish Collections.
Keywords: History of Art and Architecture, Ph.D.; Ph.D. Trinity College Dublin